The effect of prenatal stress on birth weight: Evidence from the al-Aqsa Intifada - Hani Mansour; Daniel I. Rees (Institute for the Study of Labor (IZA), 2011)
No previous study has attempted to estimate the effect of intrauterine exposure to armed conflict, a potential source of stress, on pregnancy outcomes. Drawing on data from the 2004 Palestinian Demographic and Health Survey, we examine the relationship between fatalities caused by Israeli security forces (a measure of conflict intensity) and birth weight. Our estimates suggest that first-trimester fatalities are positively related to the probability that a child weighed less than 2,500 grams at birth. This result is consistent with medical studies showing a strong negative correlation between self-reported stress during the first trimester of pregnancy and birth weight.
urn:nbn:de:101:1-201104133371
Keywords: I10; I12; 330; birth weight; prenatal stress; Israeli-Palestinian conflict; Schwangerschaft; Stress; Krieg; Politischer Konflikt; Kinder; Körpergewicht; Palästina